Adapting an Integrated Instructional Design and 3T Technology Training Model in a Software Development Environment - Galido, Adrian Paune (University of the Philippines Diliman, 2005)
XiFactors, Inc. is a product research and development company engaging in embedded system technologies and more recently software applications development. The company has existed for 15 years and has comprehensive product design and development capabilities in areas of networking, imaging, communications and a suite of other emerging technologies. The Software Development Group (Applications) was formed recently to provide a suite of products including document management solutions, web and database development, and Internet and intranet applications. Software developers work on a variety of platforms including MacOs, Windows and Unix. The software development group (SDG) management recognizes training system as an important factor in improving the performance of the organization. The software development group has operated for almost 30 months at the time of this study. The project based organizational structure is proven effective. The software development process deployed in the group was structured according to software engineering standards and practices. The training system, however, remained ad hoc. The initial training system revolved around three processes : presentation content preparation, presentation delivery, and feedback solicitation. The manner and schedule of presentation delivery was subject to the availability of a subject matter expert (SME). The absence of an SME most often resulted to a delay in the training schedule. The verification process for checking whether improvements to the training activities gathered from feedback were not defined and documented. Initial efforts on improving this concern are being spearheaded by a defined training team. These efforts prompted the proponent to propose a study on adapting an integrated Instructional Design (ID) and 3T technology training model. This was expected to provide the advantage of a systematic approach to training. Furthermore, it was anticipated to improve the proficiency of the training coordinators in addressing the training requirements of the software development group. Two models associated with developed training systems were utilized as basis of the integrated training model-the ID model and the 3T technology. Several literatures noted ID as useful in developing a more systematic approach to developing instruction. Instructional design is recognized as suitable in aid in delivering a more effective and manageable way to create training programs. The 3T technology defined a shift in responsibility of learning to the trainees themselves. 3T sets a 100 percent standard for covering the materials and ensuring that the skills incorporated in the materials are learned. The project aimed to provide an improved training management system through evaluating the use of an integrated Instructional Design (ID) and 3T technology training model on the software development group. The specific targets of the project included a) identify problems and issues in the training management system currently utilized by the software development group; b) provide a more systematic approach in the development and deployment of training system processes; and c) layout activities using the adapted training model for familiarizing succeeding members of the defined training team on the training management system of the software development group. The project expected to support the following items : a) provide a more systematic approach to the development and deployment of training activities; b) by adapting a training model, aid the training team define a structured training system; c) define the activities for preparing succeeding members of the training team in understanding the training management system. A team of five training coordinators interfacing with three project managers and twenty-seven software developers comprised the sample of this study. The software developers comprising the training coordinator team have an average of six months exposure in training development and an average length of stay of 22 months in the software development group at the time of this study. The members of the training coordinator team are select software developers commended by the Group Manager and Project Managers based on a set of criteria including a) knowledge of the basic foundation of the technical aspects of a project; b) excellent interpersonal and communication skills; and c) excellent interviewing skills. The project was undertaken over a period of seven months. The project reviewed the current group training system and adapted an integrated 1D and 3T technology training model. The intent was to evaluate whether the integrated model addressed the training improvement requirements of the software development group. A training management system upgrade and an accompanying study plan were designed and documented based on the review of the 1D and the 3T technology training model. These were evaluated in this study. The system upgrade defined four training phases-training needs assessment and planning, training design and development, training implementation, and training evaluation and maintenance. The four training phases were planned to be utilized in a sequential manner to address training requirements. The study plan aimed to familiarize members of the defined training team on concepts relating to training model and training management system. The training management system was established to plan, organize and coordinate the training system of the Software Development Group. This management system covered the activities of defining the training system and planning for adjustments as seen fit for the benefit of the organization. This training management system upgrade documentation was released to the training coordinator team for evaluation and feedback. Responses to questionnaires, presented as different sets of guides, were utilized to obtain group-related information. Checksheets were designed for and deployed to the training coordinator team to improve familiarity with concepts relating to training model and training management system. The system upgrade was deployed through a training program for training coordinators. The training coordinator training program was scheduled over a six-week period. The coordinators reviewed concepts relating to training models and training management systems on the first 3 weeks, and for the remainder of the training program applied those concepts in improving software development. The proponent and the Training Coordinator Team (TCT) lead acted as signatories for the sign-off of the checksheets utilized which included a training model review and a training management system checksheet. Complete review of the topics was ensured prior to sign-off. The training coordinators were able to achieve complete sign-off on both checksheets within the specified period. The training coordinators displayed an improved ability in designing and developing training. This was exhibited in a faster training program for software developers by an average of 2 weeks. The system upgrade was instituted simultaneously in three projects delivering a) a client-side web applications software for the Windows platform; b) a server-side web applications software; and c) further improvement on the paperless office concept. Using the same set of technical modules and hands-on exercises deployed in the previous training system, the training coordinators improved the sequencing of the training activities and at the same time shortened the length of training for software developers. The software developer training program was redesigned using the adapted training model which was in congruence with the idea of the checksheet usage from 3T technology and the phases of ID. The training management system upgrade and the study plan enabled the training coordinators to streamline the current software developer training program reducing areas where the software developers undertaking the program are inactive. Feedback from software developers pointed that the technical modules were better understood when applied immediately after covering the materials and when trainer feedback was received thereafter. The results of the study suggested that adapting the integrated 1D and 3T technology training model greatly improved the training system of the software development group in terms of improving the proficiency of the training coordinators and providing a more systematic approach to training. Results also showed that using the model shortened the length of the training program for software developers thus developers were able to participate in system implementation sooner. It was shown that the integrated 1D and 3T technology training model was effective for the software development group.